An IOT Based Framework for Group Monitoring and Irrigation Control (International Journal of Engineering and Computer Science, 2016)
vToday’s world is more dependent on the web application as it really helps people to do the work much faster and easier from anywhere on the corner of the globe. Hence, we have proposed the system which is a web based real-time application used for the development of automatic irrigation control and to help the farmer in improving the productivity of the crops. Because the system is automated there is no need of visiting the agricultural land by the farmer personally to provide the sufficient water to the crops and the system will also give the message to the farmer about the environmental conditions, so that farmer can take decision about the crops productivity and watering service. Results shows that the system is cost-effective because there is no extra expenditure required for getting and visualizing the information about environmental conditions of the agricultural field and this system will helps the farmer to increase the productivity without any effort.